Storynomics dewi taro: strategi promosi berbasis konten storynomics untuk mendukung pelestarian budaya lokal di desa wisata taro - Arini, Ni Nyoman; Putra, I Nengah Sandi Artha (Jurnal Kepariwisataan dan Hospitalitas; Vol 8 No 2 (2024): Vol.8,No.2,2024, 2024)
This research aims to explore local stories and develop a content-based promotion strategy for storynomics tourism in Taro Tourism Village. This study uses the theory of storynomics tourism and descriptive qualitative methods. Data was collected through interviews, observations, and documentation. The results of this study show that cultural elements such as myths, history, community traditions, traditional ceremonies, performing arts, agricultural systems, and natural beauty in Taro Tourism Village, can be packaged into interesting and educational content to increase tourist attraction. The application of the Multimedia Development Life Cycle (MDLC) stages in the creation of storynomics content has succeeded in creating interesting and informative narratives. This content not only provides information about the local stories of Taro Village, but also invites visitors to explore tourist attraction in more depth through 360° photos. Content distribution through websites and social media expands the reach of promotion, encourages community participation in cultural preservation, and supports sustainable tourism in Taro Tourism Village.